2013
DOI: 10.1007/s40243-013-0011-4
|View full text |Cite
|
Sign up to set email alerts
|

Transesterification of peanut and rapeseed oils using waste of animal bone as cost effective catalyst

Abstract: Heterogeneous catalysts were developed from goat animal bones for biodiesel production via transesterification process. Desirable feedstock like peanut and rapeseed oils were chosen as raw material for the transesterification process. The bone catalysts calcined at 900°C shows low crystallite size (41.47434 nm) and higher surface area (90.6523 m 2 /g) compared to catalysts calcined at other temperatures. The maximum biodiesel yield of 94 % for peanut oil and 96 % for rapeseed oil were obtained at 20:1 molar ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
1
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 24 publications
0
34
1
4
Order By: Relevance
“…23,26 Jazie et al synthesized biodiesel production from peanut and rapeseed oil using goat animal bone as a catalyst. 27 The maximum biodiesel yield of 94% and 96% for peanut and rapeseed oil, respectively, were achieved under the reaction conditions such as 1:20 molar ratio (oil/methanol), 60°C reaction temperature, catalyst concentrations of 18 wt%, and 4-hour reaction time. Smith et al synthesized the biodiesel using bovine bone catalyst and obtained the maximum yield of 97% under the optimum conditions of 1:6 molar ratio, 8 wt% of catalyst concentration, and 3-hour reaction time at 65°C.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…23,26 Jazie et al synthesized biodiesel production from peanut and rapeseed oil using goat animal bone as a catalyst. 27 The maximum biodiesel yield of 94% and 96% for peanut and rapeseed oil, respectively, were achieved under the reaction conditions such as 1:20 molar ratio (oil/methanol), 60°C reaction temperature, catalyst concentrations of 18 wt%, and 4-hour reaction time. Smith et al synthesized the biodiesel using bovine bone catalyst and obtained the maximum yield of 97% under the optimum conditions of 1:6 molar ratio, 8 wt% of catalyst concentration, and 3-hour reaction time at 65°C.…”
Section: Introductionmentioning
confidence: 93%
“…Corro et al and Obadiah et al reported that catalyst derived from animal bone remains active after 10 runs of the transesterification process of biodiesel production synthesized from waste cooking oil . Jazie et al synthesized biodiesel production from peanut and rapeseed oil using goat animal bone as a catalyst . The maximum biodiesel yield of 94% and 96% for peanut and rapeseed oil, respectively, were achieved under the reaction conditions such as 1:20 molar ratio (oil/methanol), 60°C reaction temperature, catalyst concentrations of 18 wt%, and 4‐hour reaction time.…”
Section: Introductionmentioning
confidence: 99%
“…Cu-NHAp [12] Animal bone [13] Waste animal bone [14] Artificial H 3 PO 4 /A 2 O 3 [27] Langmuir surface area (m 2 g À1 ) at P S / P 0 = 0.9814 confirmed that Al doping resulted in a more stable CWFB-HAp-Al. Also CWFB-CHAp has shown stability up to 1000°C, with total weight loss of 12.3%.…”
Section: Cfwb-hapalmentioning
confidence: 91%
“…Although they tried to prepare an acidic catalyst, however they used 25% Ammonia solution to make the solution pH 4.0, which is bit abrupt for the acid catalyst preparation process. Jazie et al [13] used waste animal bone for transesterification of peanut and rapeseed oils. Obadiah et al [14] also used waste animal bone for biodiesel production from palm oil.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, heterogeneous catalysts have the general advantage of being reused and easy to separate from the products. Sources of waste such as chicken oyster shell, egg shell, golden apple snail, mud crab shell, meretrix venus and mollusk shell as rich sources of CaO is cheap and can be utilized as heterogeneous catalyst for production of biodiesel [7]. Our previous study showed that fish bone is suitable to be used as catalyst to produce biodiesel using palm oil [8].…”
Section: Introductionmentioning
confidence: 99%